Analisis Konflik Dan Dampak Keterbelakangan Dalam Akses Jaringan Internet Dan Listrik Di Desa Terate Yang Terikat Dengan PTPN XII Kotta Blater - Della Aprilia Kartika Putri; Nanda Aulia Rahmawati; Rahayu Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Terate village, which is located near the PTPN XII Kotta Blater plantation company, is facing serious problems related to poor internet networks and electricity supplies. The aim of this research is to study the dynamics of conflict, how retarded access impacts people's lives. The analysis is based on Ralf Dahrendorf's conflict theory to understand inequality of access. This study will look at what caused conflict during the construction of internet and electricity network infrastructure in Terate Village, with special emphasis on the role of the economic power of PTPN XII Kotta Blater in causing conflict. In addition, we will investigate how limited access affects education, economic growth and social life in Terate Village. This research will use approaches such as interviews and surveys with the community to gain a better understanding of the dynamics of conflict in Terate Village. In addition, this research is expected to provide insight into the complexity of conflict and also provide recommendations with the aim of improving equality of access and quality of life.